2021
DOI: 10.1111/tmi.13569
|View full text |Cite
|
Sign up to set email alerts
|

Limited specificity of commercially available SARS‐CoV‐2 IgG ELISAs in serum samples of African origin

Abstract: Objectives Specific serological tests are mandatory for reliable SARS‐CoV‐2 diagnostics and seroprevalence studies. Here, we assess the specificities of four commercially available SARS‐CoV‐2 IgG ELISAs in serum/plasma panels originating from Africa, South America, and Europe. Methods 882 serum/plasma samples collected from symptom‐free donors before the COVID‐19 pandemic in three African countries (Ghana, Madagascar, Nigeria), Colombia, and Germany were analysed with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 20 publications
4
72
0
Order By: Relevance
“…Postinfection antibody kinetics vary by infection severity, patient age, and prior exposure, as can test performance. When we tested prepandemic samples from Juba, we found that background SARS-CoV-2 antibody reactivity was higher in Juba than in Boston, which was consistent with findings from studies conducted in other sites in sub-Saharan Africa ( 11 , 13 , 30 , 31 ). We used these negative controls to estimate test specificity, but we lacked data on the post SARS-CoV-2 infection antibody kinetics and the proportion of infections that were mild or asymptomatic in the Juba population, which led to wide variation in plausible estimates of seroprevalence, as shown in our sensitivity analyses.…”
Section: Discussionsupporting
confidence: 88%
“…Postinfection antibody kinetics vary by infection severity, patient age, and prior exposure, as can test performance. When we tested prepandemic samples from Juba, we found that background SARS-CoV-2 antibody reactivity was higher in Juba than in Boston, which was consistent with findings from studies conducted in other sites in sub-Saharan Africa ( 11 , 13 , 30 , 31 ). We used these negative controls to estimate test specificity, but we lacked data on the post SARS-CoV-2 infection antibody kinetics and the proportion of infections that were mild or asymptomatic in the Juba population, which led to wide variation in plausible estimates of seroprevalence, as shown in our sensitivity analyses.…”
Section: Discussionsupporting
confidence: 88%
“…Interpretation of SARS-CoV-2 serologic test results, except pan Igs Wanti ELISA, has been reported to be very challenging in Africa due to pre-existing cross-reactive antibodies induced by other pathogens such as non-SARS-CoV-2 human coronaviruses and malaria parasites [13]. Given the rapid decline of anti-SARS-CoV-2 nucleocapsid antibodies as compared to the anti-RBD IgG antibody 13 , we developed and optimized an in-house ELISA that detects anti-SARS-CoV-2 IgG antibodies. Our assay, unlike other commercially available serologic assays, is affordable and has been validated with a large number of Ethiopian sera from both pre-COVID-19 and COVID-19 patients from the same regions.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity has also been found in recent studies in malaria-endemic countries; two SARS-CoV-2 serological assays targeting the nucleocapsid protein had cross-reactivity among pre-pandemic samples from Nigeria with higher levels of malaria antibodies 13 . A high rate of false positives was also seen in pre-pandemic samples using commercially available ELISAs from Benin 14 and from Ghana and Nigeria 15 .…”
Section: Mainmentioning
confidence: 95%